EFEKTIVITAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DI MASA PANDEMI CORONAVIRUS DISEASE 19 (COVID-19) TERHADAP MASYARAKAT DI KABUPATEN BENGKULU TENGAH - Kiki Amaliah; Widiya N Rosari (UNIB Press, 2022)
Research on the Effectiveness of the Corporate Social Responsibility (CSR) Program in Mitigating the Impact of the COVID-19 Pandemic was conducted on communities in Regency of Bengkulu Tengah, Bengkulu Province. During the COVID-19 pandemic, many people were affected, especially the economic sector lost their jobs (termination of employment) or are unemployed, and weak public purchasing power which resulted in many businesses being closed or empty of buyers. Research is needed to study or analyze the extent of effectiveness and constraints in implementing the Corporate Social Responsibility (CSR) program during the COVID-19 pandemic so that it has an impact on increasing the welfare of the people in the Regency of Bengkulu Tengah. The research method used is empirical juridical research. The result of this research is the Program CSR during the COVID-19 pandemic in Regency of Bengkulu Tengah was considered ineffective and the obstacles faced in the CSR program were the unclear Standard Operating Procedure (SOP) for companies, the lack of socialization of CSR to the community and the absence of CSR consultants who went directly into the field to find out what we're programs needed by the community. Keywords: Corporate Social Responsibility (CSR); Covid-19; CSR Effectiveness.